The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adfm.202300575
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis‐Mediated Synergistic Therapy of Hypertrophic Scarring Based on Metal–Organic Framework Microneedle Patch

Abstract: Hypertrophic scarring, an abnormal fibroproliferative wound-healing disease, has brought tremendous burden for global healthcare systems. To date, no satisfactory treatment of hypertrophic scarring is available yet. Ferroptosis, an iron-dependent form of cell death, has attracted much attention recently for the therapy of diseases featuring iron addiction. Intriguingly, myofibroblasts derived from hypertrophic scarring are found to exhibit a high iron state which appears to be sensitive to trigger ferroptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The MPSS@ZIF-90 exhibited a promising therapeutic effect in HS treatment within a short period, while several months are required in the recently reported drug delivery systems and current clinical therapies. 4,50–52 Our investigations on experimental wound models in rabbit ears exhibited the effective treatment of MPSS@ZIF-90 in accelerating wound healing processes, and inhibiting the expression of HS-related proteins.…”
Section: Resultsmentioning
confidence: 90%
“…The MPSS@ZIF-90 exhibited a promising therapeutic effect in HS treatment within a short period, while several months are required in the recently reported drug delivery systems and current clinical therapies. 4,50–52 Our investigations on experimental wound models in rabbit ears exhibited the effective treatment of MPSS@ZIF-90 in accelerating wound healing processes, and inhibiting the expression of HS-related proteins.…”
Section: Resultsmentioning
confidence: 90%
“…Recently, MNs loaded with nanocomplex have been reported for ferroptosis-mediated synergistic wound therapy. [53] In addition, the antibacterial infection effect of MNs encapsulated with photothermal nanozyme have also been proven. [54] Encouraged by the previous works and remarkable nanocatalytic performance of the CuGQD/PdNPs@PSi in vitro, we further integrated CuGQD/PdNPs@PSi into the ultralive hyaluronic acid (HA) matrix to develop a dissolvable microneedle patch specifically for melanoma treatment.…”
Section: Fabrication and Characterization Of Cugqd/pdnps@psi Mnsmentioning
confidence: 99%
“…The depletion of GSH is the main cause of ferroptosis ( Li et al, 2023 ). Studies have shown that myofibroblasts in HTS exhibit high iron levels, which can be targeted for “Ferroptosis-mediated scarring therapy.” To this end, Zhao et al (2023) developed a new ferroptosis-based nanoplatform by combining AgNC/TRG/ZIF-8 with the GelMA MN patch. In acidic environment, ZIF-8 is easy to degrade and release Zn2+ and 2-methylimidazole ligand.…”
Section: New Technologiesmentioning
confidence: 99%